2019
DOI: 10.1038/s41375-019-0436-6
|View full text |Cite
|
Sign up to set email alerts
|

NLRP3 inflammasome couples purinergic signaling with activation of the complement cascade for the optimal release of cells from bone marrow

Abstract: The mechanisms that regulate egress of hematopoietic stem/progenitor cells (HSPCs) into peripheral blood (PB) in response to stress, inflammation, tissue/organ injury, or administration of mobilization-inducing drugs are still not well understood, and because of the importance of stem cell trafficking in maintaining organism homeostasis, several complementary pathways are believed to be involved. Our group proposes that mobilization of HSPCs is mainly a result of sterile inflammation in the bone marrow (BM) mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
56
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 51 publications
(63 citation statements)
references
References 66 publications
7
56
0
Order By: Relevance
“…Our already published results demonstrated that the Nlrp3 inflammasome plays a crucial role in the mobilization into PB of HSPCs and other BM-residing stem cells [62]. In support of this finding, the Nlrp3 inflammasome becomes activated during mobilization, both in innate immunity cells (granulocytes, monocytes, and dendritic cells) and in HSPCs in response to G-CSF or AMD3100.…”
Section: The Role Of the Nlrp3 Inflammasome In Stem Cell Mobilizationsupporting
confidence: 67%
See 1 more Smart Citation
“…Our already published results demonstrated that the Nlrp3 inflammasome plays a crucial role in the mobilization into PB of HSPCs and other BM-residing stem cells [62]. In support of this finding, the Nlrp3 inflammasome becomes activated during mobilization, both in innate immunity cells (granulocytes, monocytes, and dendritic cells) and in HSPCs in response to G-CSF or AMD3100.…”
Section: The Role Of the Nlrp3 Inflammasome In Stem Cell Mobilizationsupporting
confidence: 67%
“…Since egress of HSPCs into peripheral blood (PB) is mediated by induction of a state of sterile inflammation in the BM hematopoietic microenvironment due to innate immunity activation [44], we became interested in whether the Nlrp3 inflammasome plays a significant role in the mobilization process [62]. We also asked whether Nlrp3 inflammasome-mediated mechanisms play a role in the mobilization of other BM-residing stem/progenitor cells, such as mesenchymal stromal cells, endothelial progenitor cells, and very small embryonic-like stem cells.…”
Section: A Novel Role For the Nlrp3 Inflammasome In The Trafficking Omentioning
confidence: 99%
“…Furthermore, supporting the important role of innate immunity in mobilization, we recently demonstrated involvement of the Nlrp3 inflammasome complex in the induction of "sterile" inflammation in BM, which triggers the mobilization of HSPCs [10,11]. Based on this and our previous data we become interested in a potential role of alterative pathway of ComC activation in mobilization of HSPCs.…”
Section: To the Editorsupporting
confidence: 61%
“…In addition in pathogenesis of inflammaging are involved several danger associated molecular pattern molecules (DAMPs) including extracellular ATP, oxidatively modified DNA; and aggregated proteins released from damaged cells [105]. All these DAMPs lead to activation of the Nlrp3 inflammasome, that drives process of inflammaging in the all tissues including bone marrow [106][107][108]. Activation of Nlrp3 inflammasome leads to release from innate immunity cells two pro-inflammatory interleukins IL-1β and IL-1 [105][106][107][108].…”
Section: The Role Of Inflammaging In Pathogenesis Of Aamentioning
confidence: 99%
“…All these DAMPs lead to activation of the Nlrp3 inflammasome, that drives process of inflammaging in the all tissues including bone marrow [106][107][108]. Activation of Nlrp3 inflammasome leads to release from innate immunity cells two pro-inflammatory interleukins IL-1β and IL-1 [105][106][107][108]. While as demonstrated IL-1β signaling decreases erythropoietin secretion in the kidney [109], IL-18 induces interferon gamma (IFN-γ) expression, which along with IL-1α synergistically inhibits erythroid colony formation [110].…”
Section: The Role Of Inflammaging In Pathogenesis Of Aamentioning
confidence: 99%